2013
DOI: 10.1038/nrurol.2013.185
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of advanced technologies in prostate cancer radiotherapy

Abstract: Conventional treatment options for clinically localized, low-risk prostate cancer include radical prostatectomy, external-beam radiotherapy (EBRT) and low-dose-rate brachytherapy. Advances in image-guided radiotherapy (IGRT) since the 1980s, the development of intensity-modulated radiotherapy (IMRT) during the 1990s and evidence from radiobiological models--which support the use of high doses per fraction--have developed alongside novel advanced radiotherapy modalities that include high-dose-rate brachytherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 150 publications
(182 reference statements)
0
46
0
2
Order By: Relevance
“…Thus, long-term follow up is required to justify the increasing use of PBT for prostate cancer. It has been demonstrated that PBT is a safe and effective method for patients with localized prostate cancer (56)(57)(58)(59). However, it is necessary to further compare PBT with other treatment regimens for local prostate cancer to determine the optimal treatment regimen for different patients (60).…”
Section: Pbt For Different Cancersmentioning
confidence: 99%
“…Thus, long-term follow up is required to justify the increasing use of PBT for prostate cancer. It has been demonstrated that PBT is a safe and effective method for patients with localized prostate cancer (56)(57)(58)(59). However, it is necessary to further compare PBT with other treatment regimens for local prostate cancer to determine the optimal treatment regimen for different patients (60).…”
Section: Pbt For Different Cancersmentioning
confidence: 99%
“…treatments for low-risk prostate cancer include radical prostatectomy and radiotherapy, both of which are associated with significant morbidities. [5][6][7] In recent years, the concept of active surveillance (AS) has been adopted with the aim of monitoring clinically insignificant prostate cancer until disease progression, at which point radical prostatectomy or radiotherapy is considered. The ultimate objective is to delay or avoid the morbidities associated with radical treatments without compromising survival.…”
Section: Discussionmentioning
confidence: 99%
“…Zaorsky et al (27) reviewed the literature and concluded that PBT should not be used for patients, regardless of their disease, outside the setting of a clinical trial. At present, for prostate cancer, the ASTRO policy for PBT recommends well-designed registries and studies with sizable comparative cohorts to accelerate data collection.…”
Section: Sheets Et Al Used Surveillance Epidemiology and Endmentioning
confidence: 99%